Estrutura baseada em estados virtuais para aumento da robustez em sistemas decontrole de inversores aplicados a sistemas de geração distribuída - Kraemer, Rodrigo Antonio Sbardeloto (2020)
Considering the high insertion of distributed generation systems connected to the distribution network, there is a need to establish system control strategies in order to meet the requirements in current standards, such as NBR and IEEE. In a microgrid, the inverter systems that compose it are subject to several factors that can compromise the quality of the energy injected into the grid, such as non-linear loads and other inverters. Furthermore, variations in the grid parameters impact directly the stability of the inverter. Considering that the distributed generation (DG) system analyzed in this work, uses an LCL-type connection filter, it is necessary to implement a control structure that reduces the gain of the filter in its resonant frequency to prevent the system from becoming unstable in the presence of disturbances. Thus, after describing the microgrid under study, defining the scope and scenarios that will be considered in this work, a stabilizing structure named Virtual State Damping (VSD) is proposed. VSD has the advantage of providing flexibility to the designer when building GD stabilization filters, unlike other active damping techniques that are restricted to the physical elements of the LCL filter. Finally, the VSD design methodology is presented with the microgrid analysis through real-time emulation, implemented through Typhoon HIL, and experimental analysis through experimental prototype developed in the laboratory, demonstrating the efficiency of the proposed control structure.